1998
DOI: 10.1093/emboj/17.17.5001
|View full text |Cite
|
Sign up to set email alerts
|

The alternative product from the human CDKN2A locus, p14ARF, participates in a regulatory feedback loop with p53 and MDM2

Abstract: The two distinct proteins encoded by the CDKN2A locus are specified by translating the common second exon in alternative reading frames. The product of the α transcript, p16 INK4a , is a recognized tumour suppressor that induces a G 1 cell cycle arrest by inhibiting the phosphorylation of the retinoblastoma protein by the cyclin-dependent kinases, CDK4 and CDK6. In contrast, the product of the human CDKN2A β transcript, p14 ARF , activates a p53 response manifest in elevated levels of MDM2 and p21 CIP1 and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
944
9
18

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,060 publications
(1,031 citation statements)
references
References 80 publications
60
944
9
18
Order By: Relevance
“…The INK4a-ARF locus encodes two distinct tumour suppressors p16 INK4a (or human p15) and p19 ARF (or human homolog p14). Whereas p16 INK4a restrains cell growth through preventing phosphorylation of the retinoblastoma protein, p19 ARF (or human homolog p14) acts by attenuating MDM2-mediated degradation of p53 Stott et al, 1998) (Figure 2). Recent data indicate that MDM2 shuttles between the nucleus and the cytoplasm and that nucleo-cytoplasmic shuttling of MDM2 is essential for MDM2's ability to promote p53 degradation.…”
Section: P19arf Links the Tumour Suppressors Rb And P53mentioning
confidence: 99%
“…The INK4a-ARF locus encodes two distinct tumour suppressors p16 INK4a (or human p15) and p19 ARF (or human homolog p14). Whereas p16 INK4a restrains cell growth through preventing phosphorylation of the retinoblastoma protein, p19 ARF (or human homolog p14) acts by attenuating MDM2-mediated degradation of p53 Stott et al, 1998) (Figure 2). Recent data indicate that MDM2 shuttles between the nucleus and the cytoplasm and that nucleo-cytoplasmic shuttling of MDM2 is essential for MDM2's ability to promote p53 degradation.…”
Section: P19arf Links the Tumour Suppressors Rb And P53mentioning
confidence: 99%
“…9p21, which codes p15 INK4b , p16 INK4a and p14 ARF genes, are often observed in many cancers (Ruas and Peters, 1998). p14 ARF is an activator of p53 and indirectly induces p21 CIP1 expression (Stott et al, 1998). Defect of Ch.…”
Section: Discussionmentioning
confidence: 99%
“…8 This is particularly important as it has been shown that the ability of E2F1 to enhance the apoptotic function of p53 is independent of p19 Arf , 19 which is a transcriptional target of E2F 20 and is also an inducer of p53 through its ability to prevent Mdm2-mediated degradation of p53. 21 In the context of DNA damage, E2F is also important. In response to a genotoxic event, p53 causes a cell cycle arrest by transactivating the CDKN1A gene, encoding p21 Waf1/Cip1 thereby ensuring a G 1 arrest.…”
Section: The E2f Familymentioning
confidence: 99%